Fabrication of a high wear resistance AA7075/AL2O3 composites via liquid metallurgy process - Sivaraman, R.; Jalil, Abduladheem Turki; Aravindhan, Surendar; Nan, Zhao; Vini, M. Heydari; Daneshmand, S. (Zielona Góra: Uniwersytet Zielonogórski)
In the present study, AA7075/Al2O3 composites have been fabricated via liquid metallurgy process. AA7075 alloy and Al2O3 particles were taken as the base matrix and reinforcements, respectively. Then, contents of 3 and 6 wt. % of Al2O3 subdivisions were added into the AA7075 matrix.
Keywords: AA7075; Al2O3; wear; composites; stir casting